Volatility Integration of World GDP and World Inflation Rate with Crude Oil Prices - Vijayakumar, S.; Karthikeyan, P (Indian Journal of Finance, 2024)
Purpose : The price of crude oil directly affects inflation. The cost of products and services goes up across the economy when oil prices rise. Since both factors affected crude oil price movement, the current study focused on how variations in the global gross domestic product (GDP) and global inflation affect crude oil price volatility. Methodology : In the current study, the relationship and extended impact among a few study variables were analyzed using bivariate GARCH models (diagonal VEC GARCH and BEKK GARCH). The analysis was based on annual sample data from January 2000 to December 2022 to investigate the volatility association in the three variables, along with volatility, spillover, and the effect. Results : The study revealed the mutual relationships among world GDP, inflation, and crude oil prices. The world GDP and crude oil prices were found to have a considerable conditional correlation when bivariate GARCH models were employed. Therefore, while they showed volatility spillover in co-variance, the global GDP and inflation rate did not show volatility spillover effects on crude oil prices. A noteworthy correlation between the pace of global inflation and the price of crude oil was also discovered by the investigation. On the other hand, it is insignificant and shows a reverse impact of world GDP on the changes in crude oil prices. Additionally, the world inflation rate volatility negatively affected oil prices in the spillover effect. Implications : This study is significant from the investment point of view as various investors invest in financial instruments. This study revealed substantial information to policymakers and corporations for essential decisions regarding exploration and production activities. It also contributed to an academic pool of information domains for further research. The interplay between these factors could significantly influence economic outlooks and policy decisions globally. Value/Originality : This is the first study on crude oil, world GDP, and world inflation, as far as we know.